Goldziher's views on Arabic linguistics; an analysis of its relevance - Yaacob, Solehah@Nik Najah Fadilah (s.n, 2012)
This study aims to critically examine the alleged by Ignaz Goldzihar on the awakening of grammatical awareness on the beginning of Arabic Linguistic. Such as the vowels and harakat were not origin from Arabs but has been followed from Syria in the usage of certain signs, so he believed the differences of the three parts of speech; isim(name i.e. noun), fi'l(action i.e. verb) and harf(letter i.e. particle) which presupposes the knowledge of the Aristotelian on his book De Interpretation is attributed to 'Ali (Karrama Ilahu wajhah)